2004
DOI: 10.1007/s10029-004-0213-x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to adhesion formation: A comparative study of treated and untreated mesh products placed in the abdominal cavity

Abstract: The incidence of adhesions and work and strength of adhesion separation are reduced when using a treated mesh, compared to the untreated mesh and the control group without mesh. Parietex Composite, Parietene Composite, Bard Composix E/X, and Gore-Tex Dual Mesh were superior to Sepramesh, untreated Parietene, and the control group in the prevention of adhesion formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 10 publications
3
53
0
4
Order By: Relevance
“…Com relação à estrutura espacial da tela, observouse em diversos estudos através da microscopia eletrônica, que as telas micro porosas têm estrutura mais laminar, o que permite depósito mais regular e organizado das células mesoteliais, permitindo a formação de um neo-peritônio nos primeiros dias após a sua colocação e, assim, diminuindo a formação de aderências 5,6,9,13 . Na prótese laminar ocorre mesotelização de forma simétrica e regular ao passo que na reticular o depósito do mesotélio é irregular e desorganizado, propiciando formação de aderências nos locais descobertos por mesotélio 6,9,13 .…”
Section: Estrutura Tridimensional Da Próteseunclassified
See 3 more Smart Citations
“…Com relação à estrutura espacial da tela, observouse em diversos estudos através da microscopia eletrônica, que as telas micro porosas têm estrutura mais laminar, o que permite depósito mais regular e organizado das células mesoteliais, permitindo a formação de um neo-peritônio nos primeiros dias após a sua colocação e, assim, diminuindo a formação de aderências 5,6,9,13 . Na prótese laminar ocorre mesotelização de forma simétrica e regular ao passo que na reticular o depósito do mesotélio é irregular e desorganizado, propiciando formação de aderências nos locais descobertos por mesotélio 6,9,13 .…”
Section: Estrutura Tridimensional Da Próteseunclassified
“…Na prótese laminar ocorre mesotelização de forma simétrica e regular ao passo que na reticular o depósito do mesotélio é irregular e desorganizado, propiciando formação de aderências nos locais descobertos por mesotélio 6,9,13 . Fica claro, então, que a face laminar da tela deve ficar disposta para o interior da cavidade, isto é, em contato com as vísceras.…”
Section: Estrutura Tridimensional Da Próteseunclassified
See 2 more Smart Citations
“…Schulze et al showed that collagen sealant (a bioabsorbable material containing type-1 collagen) prevented the migration of Parietex composite mesh during an 8-week period when it was used as a fixator [21]. The signs of inflammation in the surrounding tissue, adhesions around the mesh, and strength of adhesion separation were reduced with absorbable coverage of the fixators [21,22].…”
Section: Discussionmentioning
confidence: 99%